Soto Velasco, Sebastián. Palanza, Valeria (2019): Checking Presidential Power. Executive Decrees and the Legislative Process in New Democracies (Cambridge, Cambridge University Press) 245 pp. - Soto Velasco, Sebastián (Revista Chilena de Derecho, 2021)
.